AN ANALYSIS ON SPELLING ERRORS MADE BY THE SECOND GRADE STUDENTS OF OFFICE ADMINISTRATION DEPARTMENT OF SMK N 3 PADANG IN WRITING A PERSONAL LETTER - Alfi Rahmi Rusvid; Saunir Saun; Fitrawati Fitrawati (Universitas Negeri Padang, 2016)
This research discusses about spelling errors which are committed by the students in writing a personal letter. Participants in this research are Office Administration Students in SMK N 3 Padang, XI AP 1 class which consists of 24 students. The identified problems of this research are what kinds of spelling errors—insertion, omission, substitution, and transposition errors—which are committed by the students in writing a personal letter, and what kinds of parts of speech from spelling errors which are committed by the students. The objectives of this research are to find out what kinds of spelling error which are committed by the students, and what kinds of part of speech from spelling errors which are committed by the students. Writing test is an instrument that is used in this research. The result of this research shows that students commit all kinds of spelling errors in their writing, and students’ spelling errors also occur in all kinds of parts of speech. Students’ spelling errors mostly occur in substitution error in their writing. Then, noun part is the highest part which occurs from students’ spelling errors.